2020
DOI: 10.1186/s12940-020-00659-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of environmental manganese exposure and associations with childhood neurodevelopment: a systematic review and meta-analysis

Abstract: Background Although prior studies showed a correlation between environmental manganese (Mn) exposure and neurodevelopmental disorders in children, the results have been inconclusive. There has yet been no consistent biomarker of environmental Mn exposure. Here, we summarized studies that investigated associations between manganese in biomarkers and childhood neurodevelopment and suggest a reliable biomarker. Methods We searched PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 103 publications
(325 reference statements)
1
34
0
2
Order By: Relevance
“…Mn neurotoxicity is also known to affect neurodevelopment [ 19 ]. Specifically, maternal or early-life Mn exposure was shown to be associated with poorer cognitive and behavioral performance in children under six years old [ 20 ]. However, in view of the essentiality of physiological Mn levels and its toxicity upon overexposure [ 21 ], the association between Mn and adverse neurodevelopmental outcome may be U-shaped [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mn neurotoxicity is also known to affect neurodevelopment [ 19 ]. Specifically, maternal or early-life Mn exposure was shown to be associated with poorer cognitive and behavioral performance in children under six years old [ 20 ]. However, in view of the essentiality of physiological Mn levels and its toxicity upon overexposure [ 21 ], the association between Mn and adverse neurodevelopmental outcome may be U-shaped [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is our reliance on blood as a biomarker for manganese and mercury, as other biological matrices might be better biomarkers of exposure. For instance, a review and meta-analysis has concluded that hair was a better biomarker of exposure to manganese than blood [35]. Likewise, to the extent that the largest and most concerning form of mercury exposure is methylmercury, measurements made in hair might be more useful in future studies aimed at detecting neurofunctional effects resulting from overexposure to this metal [36].…”
Section: Discussionmentioning
confidence: 99%
“…Given the link emerging between inhaled PM and its metal constituents and neurological health, this section will review recent information in this area to help delineate research pathways (Table 1). Several researchers have studied the association between airborne Mn exposure and neurodevelopmental outcomes among children [33]. A 2018 cross-sectional study found a significant negative association between airborne Mn exposure and Full Scale IQ (β = −1.91, p < 0.05; β and p refer to the regression coefficient and statistical significance, respectively) among 106 children ages seven to nine living in East Liverpool, Ohio, which hosts both a hazardous waste incinerator and a Mn processor [34].…”
Section: Pm and Mental Health: Epidemiological Studiesmentioning
confidence: 99%